2012
DOI: 10.1371/journal.pone.0037357
|View full text |Cite
|
Sign up to set email alerts
|

Altered Risk-Based Decision Making following Adolescent Alcohol Use Results from an Imbalance in Reinforcement Learning in Rats

Abstract: Alcohol use during adolescence has profound and enduring consequences on decision-making under risk. However, the fundamental psychological processes underlying these changes are unknown. Here, we show that alcohol use produces over-fast learning for better-than-expected, but not worse-than-expected, outcomes without altering subjective reward valuation. We constructed a simple reinforcement learning model to simulate altered decision making using behavioral parameters extracted from rats with a history of ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 34 publications
8
46
2
Order By: Relevance
“…We have further demonstrated that increased risk preference may result from a selective defect in reinforcement learning (Clark et al, 2012) and that this is a specific consequence of alcohol exposure during adolescence, as identical exposure in adults does not produce this effect (Schindler et al, 2014). The mesolimbic dopamine system is implicated in reinforcement learning, goal-directed behavior, and motivational processes, including those for abused substances (Everitt and Robbins, 2005;Kelley, 2004;Robinson and Berridge, 1993;Salmone and Correa, 2012;Schultz, 2007).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…We have further demonstrated that increased risk preference may result from a selective defect in reinforcement learning (Clark et al, 2012) and that this is a specific consequence of alcohol exposure during adolescence, as identical exposure in adults does not produce this effect (Schindler et al, 2014). The mesolimbic dopamine system is implicated in reinforcement learning, goal-directed behavior, and motivational processes, including those for abused substances (Everitt and Robbins, 2005;Kelley, 2004;Robinson and Berridge, 1993;Salmone and Correa, 2012;Schultz, 2007).…”
Section: Introductionmentioning
confidence: 79%
“…The gelatin was made available 24 h/day in addition to ad libitum water and chow, and the jars were replaced with fresh gelatin every day. Alcohol and control gelatin was prepared as previously described (Clark et al, 2012;Nasrallah et al, 2009). Upon completion of the 20-day alcohol and control exposure, jars were removed and the rats were monitored daily for withdrawal symptoms.…”
Section: Alcohol Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is alarming that even moderate levels of intake, when consumed chronically during adolescence, exerted significant effects on both behavior and neurophysiology. While the gelatin vehicle used here is becoming increasingly common (Clark et al, 2012;Nasrallah et al, 2009Nasrallah et al, , 2011Peris et al, 2006), it is still a relatively new consumption model. In our hands, animals consuming control gelatin ate considerably more gelatin than both the alcohol groups.…”
Section: Discussionmentioning
confidence: 99%
“…Here, following the adolescent period, alcohol was no longer given to rats, and we examined preferences for risky payoffs across a range of probabilities, while simultaneously recording OFC activity using in vivo electrophysiology. Previous studies have shown enhanced risk-preference associated with altered neural signaling following similar adolescent alcohol consumption (Clark et al, 2012;Nasrallah et al, 2009Nasrallah et al, , 2011. We therefore hypothesized that greater modulation of OFC activity in response to rewards under conditions of risk would be associated with enhanced preference for the risky choice option across levels of risk.…”
Section: Introductionmentioning
confidence: 98%